Performance in vitro e in vivo de sistemas adesivos universais em diferentes estratégias de condicionamento da dentina - Follak, Andressa Cargnelutti (2019)
The new generation of adhesive systems, called as "universal adhesives" or "multi-mode", are adhesives which can be used in both self-etch (SE) or etch-and-rinse (ER) strategies. Two studies related to these materials are presented. The aim of the first paper was to evaluate immediate and 1 year bond strength of universal adhesives to sound and cariesaffected dentin, using both SE and ER strategies. The universal adhesives tested were: Scotchbond Universal, All - Bond Universal, Prime & Bond Elect. As controls were used the adhesives Adper Single Bond 2 and Clearfil SE Bond, for ER and SE strategies respectively. They were applied following the manufacturers' instructions and a composite resin (Z250) block was built on dentin. Caries-affected dentin was artificially obtained by pH cycling for 14 days. Stick-shaped specimens were obtained (0.8 mm²) and submitted to microtensile test immediately or after 1 year of water storage. The data obtained in MPa were submitted to 3- way ANOVA for repeated measures and Post-hoc Tukey's test (α = 5%). Significant crossinteraction among the three factors (material x strategy x time) was found on both sound (p=0.002) and caries-affected dentin (p=0.009) analyses. Pronounced degradation was observed for all groups after one year on caries-affected dentin. In sound dentin, only the universal adhesives used in SE mode and the control adhesives were able to maintain bond stability after 1 year. Thus, the universal adhesives were not able to maintain bond stability in caries-affected dentin. On sound dentin, the self-etching strategy seems to be the best approach to maintain bond stability. The second paper is a randomized clinical trial that aimed to evaluate the longevity of non-carious cervical lesions restorations (NCCL) using two universal adhesive systems: Prime&Bond Elect (PB) and Scotchbond Universal (SBU) under different application strategies (ER and SE). Fifty-four participants who fit into the eligibility criteria (at least 1 tooth with LCNC, caries-free, non-retentive, with a depth greater than 1mm) were selected. Individuals who presented teeth without pulp vitality, without presence of an antagonistic tooth, previous restoration report, orthodontic treatment, smokers, patients with severe bruxism, extremely poor oral hygiene and / or with severe or chronic periodontal disease were excluded. Two hundred and eleven teeth were restored according to the experimental groups: PB-ER, PB-SE, SBU-ER and SBU-SE, with composite resin, by 2 previously trained operators. A single trained and calibrated examiner evaluated restorations after 1 week (baseline) and 6 months, using the modified USPHS and FDI evaluation criteria. The obtained data were tabulated and submitted to Kruskal-Wallis and Mann-Whitney tests to compare the failures among experimental groups. Statistical difference was found between the groups in regard to failures for both evaluation criteria. The PB-SE group had significantly more failures than the other experimental groups. Thus, the clinical performance of Prime & Bond Elect was dependent on the application strategy, and a poorer performance was found for the self-etch strategy.